2022
DOI: 10.3758/s13421-022-01273-7
|View full text |Cite
|
Sign up to set email alerts
|

Does testing enhance new learning because it insulates against proactive interference?

Abstract: Taking a test on previously learned material can enhance new learning. One explanation for this forward testing effect is that retrieval inoculates learners from proactive interference (PI). Although this release-from-PI account has received considerable empirical support, most extant evidence is correlational rather than causal. We tested this account by manipulating the level of PI that participants experience as they studied several lists while receiving interpolated tests or not. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…This finding thus places an important constraint on the strategy-change account, such that interim testing might affect learners’ subsequent retrieval strategies (Chan et al, 2020; Chan, Manley, et al, 2018; Dang et al, 2021), but leaving the encoding strategies unchanged. Consistent with this idea, a recent study by Ahn and Chan (2022) suggested that strategy change may occur during retrieval rather than encoding. Their participants studied several category word lists arranged with the same category words blocked together (i.e., blocked) or with a mixture of different category words per list (i.e., intermixed).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This finding thus places an important constraint on the strategy-change account, such that interim testing might affect learners’ subsequent retrieval strategies (Chan et al, 2020; Chan, Manley, et al, 2018; Dang et al, 2021), but leaving the encoding strategies unchanged. Consistent with this idea, a recent study by Ahn and Chan (2022) suggested that strategy change may occur during retrieval rather than encoding. Their participants studied several category word lists arranged with the same category words blocked together (i.e., blocked) or with a mixture of different category words per list (i.e., intermixed).…”
Section: Discussionmentioning
confidence: 76%
“…Their rationale was that presenting the same category words consecutively would encourage relational encoding even in the absence of testing, which should in turn reduce the performance gap between test and restudy. However, Ahn and Chan (2022) found that the forward testing effect was unaffected by category arrangements, which suggests that testing may not affect how participants encode subsequent materials.…”
Section: Strategy-change Accountmentioning
confidence: 88%
See 1 more Smart Citation
“…With respect to the forward testing effect, Yang et al (2021) discuss four mechanisms: (a) testing reduces proactive interference by inducing context changes, (b) testing leads to a more effective strategy, (c) testing resets the encoding process leaving greater capacity for subsequent encoding, and (d) testing leads individuals to invest more effort (see Yang et al, 2018, for other potential mechanisms). Yang et al (2021) provide compelling evidence for (a; but see Ahn & Chan, 2022) and (b) but not (c) and did not test (d). Evidence for the latter (i.e., testing leads to increases in effort) was provided by Yang et al (2019), who demonstrated that study time decreased with each list in a setting with no tests but stayed more constant in a setting with tests.…”
Section: Interpolated Testingmentioning
confidence: 83%
“…Because most existing studies were not explicitly designed to examine the relationship between retrieval practice performance and the testing effect, variations in retrieval practice performance coincided with changes in task demands. These changes might alter a learner’s behavior or strategies (Ahn & Chan, 2022, 2023; Cho & Neely, 2017), which could have downstream consequences on final test performance and the testing effect that are independent of retrieval practice performance per se. For example, recalling materials collaboratively (Vojdanoska et al, 2009) can alter how students approach a retrieval task and promote processes that are otherwise absent during individual recall (e.g., collaborative inhibition; Blumen & Rajaram, 2008).…”
Section: Theoretical Considerationsmentioning
confidence: 99%